Species of Padina (Dictyotales, Phaeophyceae) in tropical Mexican waters based on molecular-assisted taxonomy. Issue 6 (1st November 2016) - Díaz-Martínez, Sergio; Zuccarello, Giuseppe C.; Chávez, Gerardo A Salazar; Pedroche, Francisco F.; Avila-Ortiz, Alejandrina G.
Abstract: Molecular-assisted alpha taxonomy has provided novel ways of exploring biodiversity, and is of great help in taxa where morphology alone is not sufficient to ensure accurate species recognition or delimit species boundaries. Here, we use this approach to assess the taxonomy of Padina Adanson (Dictyotales, Phaeophyceae), a common brown algal genus in Mexican waters. Numerous individuals of Padina from Pacific and Atlantic tropical coasts were analysed using sequences of psb A, cytochrome c oxidase subunit I, and cox 3 to determine evolutionary significant units or putative species. Then, cox 3 sequences of some individuals of each group were analysed with a large number of sequences available in Genbank using the generalized mixed Yule coalescent and Poisson tree processes models for species delimitation. Each sample was identified using the original and the most common descriptions in the region. Last, the results were evaluated looking for correlations between the molecular and morphological data. We concluded that at least 12 Padina species occurred in Mexican waters, 10 from samples here revised and 2 inferred from Genbank sequences. The study not only revealed the existence of well-identified species, but also the existence of cryptic and polymorphic species, confirming the importance of reassessing type material for proper delimitation and nomenclature. Finally, the evidence supported the independent status of Padina ramonribae Avila-Ortiz, Pedroche & Díaz-Martínez, which is validated here.